Metabolic precision labeling enables selective probing of O-linked N-acetylgalactosamine glycosylation - Debets, Marjoke F.; Tastan, Omur Y.; Wisnovsky, Simon P.; Malaker, Stacy A.; Angelis, Nikolaos; Moeckl, Leonhard K.R.; Choi, Junwon; Flynn, Helen; Wagner, Lauren J.S.; Bineva-Todd, Ganka; Antonopoulos, Aristotelis; Cioce, Anna; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2020)
Protein glycosylation events that happen early in the secretory pathway are often dysregulated during tumorigenesis. These events can be probed, in principle, by monosaccharides with bioorthogonal tags that would ideally be specific for distinct glycan subtypes. However, metabolic interconversion into other monosaccharides drastically reduces such specificity in the living cell. Here, we use a structure-based design process to develop the monosaccharide probe N-(S)-azidopropionylgalactosamine (GalNAzMe) that is specific for cancer-relevant Ser/Thr(O)-linked N-acetylgalactosamine (GalNAc) glycosylation. By virtue of a branched N-acylamide side chain, GalNAzMe is not interconverted by epimerization to the corresponding N-acetylglucosamine analog by the epimerase N-acetylgalactosamine-4-epimerase (GALE) like conventional GalNAc-based probes. GalNAzMe enters O-GalNAc glycosylation but does not enter other major cell surface glycan types including Asn(N)-linked glycans. We transfect cells with the engineered pyrophosphorylase mut-AGX1 to biosynthesize the nucleotidesugar donor uridine diphosphate (UDP)-GalNAzMe from a sugar- 1-phosphate precursor. Tagged with a bioorthogonal azide group, GalNAzMe serves as an O-glycan-specific reporter in superresolution microscopy, chemical glycoproteomics, a genome-wide CRISPRknockout (CRISPR-KO) screen, and imaging of intestinal organoids. Additional ectopic expression of an engineered glycosyltransferase, "bump-and-hole" (BH)-GalNAc-T2, boosts labeling in a programmable fashion by increasing incorporation of GalNAzMe into the cell surface glycoproteome. Alleviating the need for GALE-KO cells in metabolic labeling experiments, GalNAzMe is a precision tool that allows a detailed view into the biology of a major type of cancerrelevant protein glycosylation.
Created from Fastlane, Scopus look-up
Keywords: Bioorthogonal; Glycosylation; Glycosyltransferase; Mucin